On the Impact of Brazil's Largest Recent Oil Spill on Regional Oceans - Figueiredo Mendes, Liana de; Beck Eichler, Patrícia Pinheiro; Leite, Tatiana; Alves Bennemann, Ana Beatriz; Souza Melo, Clara de; Lima Ferreira, Andressa; Ltaif Garcia, Khalil Bow; Nascimento Silva, Luzia Liniane do; Paul Barker, Christofer; Vital, Helenice; Gomes, Moab Praxedes; M. Lopes, Priscila F. (Sustainable Marine Structures, 2021)
In 2019, an oil spill in Brazil, of unknown origin, severely impacted coastal environs with the worst environmental disaster ever recorded in any tropical coastal region globally severely damaging South Pirangi Reef area in the state of Rio Grande do Norte (RN). Here we discuss acute and chronic impacts including chemical contamination and economic consequences all over the world and show some evidence of the oil spill in this biodiverse area. Moreover, the lapse between the moment of the disaster, and the action to manage it, was hampered by a political agenda coinciding with local and global tragedies that redirected public attention. Meanwhile almost 2 years have passed still without the offending party identification or culpability; and poor communities may continue to absorb its deleterious impacts for decades without consideration or compensation. This disaster occurred during the Brazilian government’s current issues involving extensive environmental mismanagement, resulting in a slow response from an inept system. It is with urgent necessity to spotlight this tragedy in this unique and sensitive reef habitat experiencing the ongoing damaging effects that include socio-economic losses not yet addressed. ER